Unveiling the Mechanism of Water-Triggered Diplex Transformation and Correlating the Changes in Structures and Separation Properties - Cao, Li-Hui; Wei, Yong-Sheng; Xu, Hong; Zang, Shuang-Quan; Mak, Thomas C. W. (Advanced functional materials, 2015)
Recently, great attention has been devoted to the initial and final structures of single‐crystal to single‐crystal (SCSC) transformations and dissolution‐recrystallization structural transformations (DRSTs), whereas the isolation and characterization of crucial intermediates and the unequivocal mechanism of the dynamic conversion process receive comparatively little consideration. Herein, a CuII‐based porous coordination polymer (PCP), which possesses a Kagomé lattice, is solvothermally synthesized. Triggered by water, the 2D Kagomé lattice (PCP‐1) primarily undergoes a reversible SCSC transformation to a distorted Kagomé intermediate (PCP‐2), which is followed by a DRST process to form a 3D NbO framework (PCP‐3) in situ. To the best of our knowledge, this is the first demonstration of a mixed SCSC and DRST transformation process. Notably, the sequential transformations result in the formation of the intermediate and the final product, which could not be obtained by direct synthesis. Regarding the intermediate, we have characterized the transformation separately and propose a plausible mechanism. More interestingly, the adsorption isotherms of water, methanol, and ethanol for the activated materials are distinctly different from one another. PCP‐2′ can uptake all three vapors with different adsorption capacities; however, the 3D transformed material PCP‐3′ only significantly absorbs water, which is concomitant with an amorphous‐to‐crystalline transformation, leading to the selective extraction of water from alcohol. A water‐triggered diplex structural transformation is successfully implemented in porous coordination polymers (PCPs), the mechanism of which is definitely clarified by the isolated and characterized intermediate. More excitingly, thanks to its high‐efficiency separation of water from alcohol the final product has a myriad of potential applications in separation technology.